2011
DOI: 10.1155/2011/381429
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Hope on GPA and Retention among College Undergraduate Students on Academic Probation

Abstract: This study analyzed the impact of hope on the academic achievement and retention of 235 students on academic probation at a private Northeastern university. Probationary students were enrolled in a mandatory online course designed to facilitate academic and nonacademic skills, to improve student GPAs and overall retention. The Hope Scale (Snyder et al. (1991)) was administered to identify whether students with greater levels of hope would experience an increase in academic success upon completion of the course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Hope-based interventions have been found to improve levels of hope while reducing symptoms of anxiety (Cheavens et al, 2006). Programs that focus on building hope should be embedded at post-secondary institutions to reduce anxiety and support academic gains in students' lives (Seirup & Rose, 2011).…”
Section: Modifiable Factors Of Interestmentioning
confidence: 99%
“…Hope-based interventions have been found to improve levels of hope while reducing symptoms of anxiety (Cheavens et al, 2006). Programs that focus on building hope should be embedded at post-secondary institutions to reduce anxiety and support academic gains in students' lives (Seirup & Rose, 2011).…”
Section: Modifiable Factors Of Interestmentioning
confidence: 99%
“…Furthermore, Siu et al (2014) propounded that self-efficacious students are more willing to do their assignments and absorb materials more easily and effectually. With regard to the second and third subconstructs, both optimism and hope are said to be highly correlated with more efficient academic performance (Gilman, Dooley, & Florell, 2006;Rand, Martin, & Shea, 2011;Seirup & Rose, 2011;Solberg, Evans, & Swgerstrom, 2009;), and also with successful graduation (Seirup & Rose, 2011) since optimistic learners are more willing to take and overcome challenges (Carver & Scheiver, 1998), and hopeful students pursue their goals more enthusiastically (Snyder, Rand, & Sigmon, 2002). Finally, the last component of PsyCap, resilience, is to a great extent associated with persistence, active participation, and adaptation (Masten & Reed, 2002), and also the academic success of resilient individuals has been found inevitable.…”
Section: Psychological Capitalmentioning
confidence: 99%
“…Krumrei-Mancuso et al (2013) noted that factors such as academic self-efficacy were predictive of students' GPA when controlling for factors such as demographics. Similarly, factors such as hope (Seirup & Rose, 2011), goal-setting (Morisano et al, 2010), and institutional connectedness (Tinto, 1975) have shown promise for student retention and success. However, limitations still exist regarding the potential generalizability of some of these models with regard to more diverse and non-traditional populations of students (Davidson & Wilson, 2013), and there still remains a gap in understanding what truly works.…”
Section: Introductionmentioning
confidence: 99%